Penyelesaian gugatan malpraktek - Djuharto S. Sutanto (JURNAL WIDYA MEDIKA, 2014)
Several unsuccessful effort of any doctor in overcoming disease in patients, in this era of “litigious society” tends to encourage some patients in resolving their problems at the green table with a malpractice lawsuit. However, the case settlement outsidethe court of justice is much more efficient and affordable. The ability of a doctor in court to face the judge or opposing patient legal counsel or attorney is very weak. Doctors who will go on trial should also be prepared emotionally and psychologically